Repositioning autologous stem cell transplantation in the management of newly diagnosed multiple myeloma - Crusoe, Edvan; Costa, Luciano (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
.